Participation Structure and Incidental Focus on Form in Adult ESL Classrooms. Issue 4 (30th August 2013) - Nassaji, Hossein
Abstract : This study examined the role of incidental focus on form (FonF) in adult English‐as‐a‐second‐language classrooms. Specifically, it explored the extent to which the amount, type, and effectiveness of FonF were related to differences in classroom participation structure, that is, the organization of classroom talk within which FonF may occur. The data consisted of 54 hours of audio‐ and video‐recorded classroom interaction collected over two 12‐week semesters from 35 lessons at three levels of language proficiency: beginner, intermediate, and advanced. The data were transcribed and coded in terms of types of FonF (reactive vs. preemptive, and student vs. teacher initiated) and types of participation structure (whole class, small group, and individual one on one). Individualized posttests were developed and administered to each student 1 week after each classroom observation to assess the effectiveness of FonF. The results revealed that incidental FonF occurred rather frequently in all classrooms but its occurrence varied depending on the type of participation structure. The results also demonstrated a relationship between participation structure and the effectiveness of FonF as well as an interaction between participation structure and class levels. These findings highlight the role of classroom participation structure as an important contextual factor that may impact the provision and success of incidental FonF.